PENGALAMAN MENGAJAR GURU SEKOLAH MENENGAH KEJURUAN DI INDONESIA PADA PANDEMI COVID-19 - Fatin Afifah; Sri Sumarni; Fajar Danur Isnantyo (LPPM Universitas Negeri Jakarta, 2022)
This study aims to discover the teaching experience of a Vocational High School teacher in the Modeling and Building Information Design Program at a school in Indonesia during the covid-19 pandemic. This research is a qualitative research with a narrative approach. Retrieval data using documentation, interviews, and observations. The data was analyzed using content analysis techniques with QSR Nvivo 12+. This study describes the implementation of online theoretical and practical learning during the covid-19 pandemic, the obstacles experienced by teachers during online learning, and the strategies used by teachers to overcome learning obstacles. It is hoped that the results of this research can be a consideration for teachers and schools in determining the policies that are applied so that online learning can run optimally.